Determining the Effect of Triclosan on the Growth of Cancer Cells - Alf, Linda (My University, 2013)
Environmental estrogens may be naturally occurring (e.g. phytoestrogens)or man-made (e.g., xenoestrogens). They mimic the effects of estrogen by binding to ERs (estrogen receptor) and modeling similar mechanisms of action. Triclosan is an antibacterial and antifungal agent included as an active ingredient in many products such as antibacterial soaps and personal care products. Triclosan has also been recently identified as a xenoestrogen. The purpose of this study was to test whether triclosan stimulates proliferation of tumor cells that express ERs.
Color poster with text, diagrams, graphs, and images.
Keywords: Cancer cells--Growth; Antibacterial agents--Carcinogenicity; Antifungal agents--Carcinogenicity; Estrogen--Environmental aspects; Posters